The Financial crisis : lessons for international macroeconomics - Bussière, Mattieu [et al] (2013)
Presents a summary of the key mechanisms at play during the crisis. Addresses the question of crisis transmission across borders, with a focus on international trade and financial institutions. Discusses recent advances in the analysis of sovereign default risk and concludes with a discussion of policy responses to the crisis.